Pengembangan Modul Ajar Pendidikan Agama Islam dengan Pendekatan Deep Learning dalam Kurikulum Merdeka pada SDIT Luqman Al Hakim Surakarta - Yadi, Yadi; Subando, Joko (TSAQOFAH, 2026)
Learning in Islamic Religious Education (Pendidikan Agama Islam, PAI) at the primary school level remains largely oriented toward memorization and superficial understanding, and therefore does not yet fully support meaningful learning as required by Kurikulum Merdeka. This study aimed to develop a PAI teaching module based on a deep learning approach for the implementation of Kurikulum Merdeka at Sekolah Dasar Islam Terpadu (SDIT) Luqman Al Hakim Surakarta. The study employed a research and development (R&D) method using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. Data were collected through document analysis, interviews, questionnaires, and observations. The findings showed that the developed deep learning–based PAI teaching module was judged valid by content and design experts, was practically applicable for teachers, and was found to be effective, on a limited scale, in enhancing students’ engagement and understanding. Accordingly, this teaching module is feasible for use as a PAI learning resource within the framework of Kurikulum Merdeka in primary schools.